Modeling and calculation of temperature distribution along the length of a wire studying problems the capacity of power transmission lines near contact connections - V. M. Trotsenko; S. S. Girshin; E. V. Petrova; V. N. Goryunov; D. G. Safonov (Омский научный вестник)
The article has obtained an analytical solution to the thermal conductivity equation for the contact connection of long sections of overhead lines, and also considered the case for a line with two short and two long sections, which makes it possible to take into account distributed defects and clamp sizes. The application of the obtained mathematical model to determine the temperature of an overhead power line near contact connections is shown. A comparative analysis of the temperature values in the power line, calculated using the created mathematical model, with published data obtained based on finite element modeling using the results of a physical experiment is performed. It has been shown that heating of contact connections can significantly limit the throughput of lines even at an acceptable level of contact resistance. This makes relevant the tasks of calculating the temperature of contact connections of power lines and clarifying permissible currents taking into account the influence of transient contact resistances.